Trends in the development of entrepreneurship in the sphere of banking services - R. M. Khakimov (Путеводитель предпринимателя)
The article deals with the concept of entrepreneurship within banking, Bank enterprise process notion, formulated the basic directions of development of business of commercial banks activity.